Coordenação entre política fiscal monetária no regime de metas de inflação - Prado, Roberto de Faria e Almeida (2008)
This dissertation deals with the coordination between monetary policy and fiscal policy in Brazil. The work aims to test the hypothesis that aggregate demand is affected by fiscal policy in Brazil between 1995 through 2006. To that end, the paper estimates an IS curve for Brazil in this period, including tax explanatory variables. The result is that there is statistical evidence that the output gap relative to potential output (from now on the product gap) is dependent (positively) government spending level and (negatively) the collection of the public sector. Moreover, as the theory predicts, government spending has an effect (in magnitude) more intense than government revenues, so that both the level of the primary surplus, as the size of government in proportion to GDP impact on aggregate demand. Thus, assuming that the convergence of real exchange rate via uncovered interest parity rate has been lagging in the period under review, fiscal policy may have contributed to maintenance of real interest rate above the equilibrium level for the period in question.